Modeling of photonic crystal fiber using boundary element method - Wang, Xiaoyan. (2008)
In this thesis, the constant-element full-vector Boundary Element Method (BEM) and the Multiple Reciprocity Boundary Element Method (MRBEM) based on transverse magnetic fields are formulated. These techniques are applied to the analysis of the Photonic Crystal Fibers (PCF). Boundary Element Method is a simple and efficient numerical method because it only requires evaluation of the integrals along the boundaries, the mesh is extremely easy and straightforward; the matrix size is very small; it is able to deal with any arbitrary structures. Moreover, because Green’s function for 2-D Helmholtz equation is used as the weighting function, Absorbing Boundary Conditions (ABC) or Perfectly Matched Layer (PML) is not needed.